THE EFFECTIVENESS OF USING ENGLISH SUB-TITLE VIDEO AS ALTERNATIVE MEDIA IN LEARNING READING NARRATIVE FOR TEN GRADERS OF SMAN 1 KUTOREJO (RETAIN, 2013)
English has four skills, one of them is reading. Reading is a complex activity in which uses perception and thought (Elizabeth, 2003:6). According of the syllabus of ten graders of senior High school, reading has some text, one of them is narrative. Narrative has purpose to entertain readers. To build of understanding can be done by some reading strategies. One of them is comprehension reading, comprehension is how the readers to construct the meaning by filling gap between previous experience, prior knowledge then the material of reading, thus readers will get the comprehension based on text reading that they read. To develop reading habit, many researcher use technology to improve it, one of them is used video and it also has sub-title to read and to comprehend. Thus to explore of knowledge of the students on reading by video sub-title or caption, the researcher must ask students to concern only in sub-title then giving them a task of comprehension to measure how far they comprehend of text. The researcher composes one statement of the problem, that “is there a significant difference in terms of reading ability of narrative story between the student who are reading sub-title video as an alternative media than those who are not in that way?”. The research conducts in ten graders of SMAN 1 kutorejo by using video of narrative as alternative media in reading by reading sub-title. The expectation of researcher by using caption video in learning narrative reading is hopefully attracting students in learning activity thus students will not bore by reading which uses text book in all of their learning day in school and hopefully by reading caption video teacher can improve their teaching activity, in effect it can build new method in learning activity. Since